Characterization of a novel thermostable l-rhamnose isomerase from Thermobacillus composti KWC4 and its application for production of d-allose. (February 2017) - Xu, Wei; Zhang, Wenli; Tian, Yuqing; Zhang, Tao; Jiang, Bo; Mu, Wanmeng
Graphical abstract: Highlights: Ad -allose-producing L-RI was characterized from T. composti KWC4. T. composti L-RI showed maximum activity at 65 °C and pH 7.5. It displayed promising thermostability and a relatively wide pH spectrum. T m of T. composti L-RI was increased by 3 °C in presence of Mn 2+ . It produced 23.30%d -allose as the sole product fromd -allulose. Abstract: d -Allose was considered as a kind of rare sugars with testified potential medicinal and agricultural benefits.l -Rhamnose isomerase (L-RI, EC 5.3.1.14), an aldose-ketose isomerase, played a significant part in producing rare sugar. In this article, a thermostabled -allose-producing L-RI was characterized from a thermotolerant bacterium, Thermobacillus composti KWC4. The recombinant L-RI was activated obviously in the presence of Mn 2+ with an optimal pH 7.5 and temperature 65 °C. The Michaelis-Menten constant ( K m ), turnover number ( k cat ) and catalytic efficiency ( k cat / K m ) forl -rhamnose were 33.8 mM, 1189.8 min −1 and 35.2 min −1 mM −1, respectively. At a higher temperature, Mn 2+ played a pivotal role in strengthening the thermostability of T. composti L-RI. The differential scanning calorimetry (DSC) results showed the denaturing temperature ( T m ) of T . composti L-RI was increased by 3 °C in presence of Mn 2+ . Although the T . composti L-RI displayed the optimum substrate asl -rhamnose, it could also effectively catalyze the isomerization betweend -allulose andd -allose. When the reaction reached equilibrium, the sole productd -allose was produced from D-alluose by T. composti L-RI.